SISTEM INFORMASI PEMESANAN BUSANA MUSLIM SECARA ONLINE BERBASIS WEB - Saputra, Elin Panca (www.bsi.ac.id, 2016)
To support the needs of the community in the field of fashion certainly has a high level in lifestyle, in every major city in the country. Along with the advanced online trading and the need for fast and accurate information, the information may have been connected to each other to form a network so vast. With a flurry of society, especially in big cities, it will be difficult to menyempati clothing buyer will need to meet everyday needs. As well as to order clothing in a way offline to visit fashion shops which will be costly and time consumed much more will be released, the author here to provide solutions that can simplify ordering clothes online by creating an application ordering clothing online with method web-based, where customers can order the clothes either via a computer, laptop or mobile phone connected to the internet. Of course it would be easier for shoppers to order online with a Muslim fashion does not cost very much greater. With the presence of this application would make it easy for the user and can meet the needs in the community.Keywords: Systems, Clothing Muslim